Differential regulation of IFNα, IFNβ and IFNε gene expression in human cervical epithelial cells - Jennifer Couret; Carley Tasker; Jaeha Kim; Tiina Sihvonen; Saahil Fruitwala; Alison J. Quayle; Pierre Lespinasse; Debra S. Heller; Theresa L. Chang (Cell & Bioscience, 2017)
Abstract Interferonε (IFNε) is a unique type I IFN that has distinct functions from IFNα/β. IFNε is constitutively expressed at mucosal tissues, including the female genital mucosa, and is reported to be modulated by estrogen and seminal plasma. However, its regulation by cytokines, including TNFα, IL-1β, IL-6, IL-8, IL-17, IL-22 and IFNα, which are commonly present in the female genital mucosa, is not well documented in freshly isolated primary cervical cells from tissues. We determined the effect of these cytokines on gene expression of type I IFNs in an immortalized endocervical epithelial cell line (A2EN) and in primary cervical epithelial cells. Several pro-inflammatory cytokines were found to induce IFNε, and TNFα induced the strongest response in both cell types. Pretreatment of cells with the IκB inhibitor, which blocks the NF-κB pathway, suppressed TNFα-mediated IFNε gene induction and promoter activation. Expression of IFNα, IFNβ, and IFNε was differentially regulated in response to various cytokines. Taken together, our results show that regulation of these IFNs depends on cell type, cytokine concentration, and incubation time, highlighting the complexity of the cytokine network in the cervical epithelium.